Extraction of Lactic Acid from Corn Kernels by Streptococcus Thermophilus Fermentation - Amaraweera, A.P.S.M.; Senevirathna, M.A.S.R.; Singhalage, I.D. (University of Jaffna, 2022)
Lactic acid is used in pharmaceutical, cosmetic and polymer industries. Lactic acid can be synthesized by fermenting glucose obtained from the hydrolysis of starch. In the present study, powdered corn kernels were hydrolyzed by α-amylase under optimized stirring time (1.5 hrs.), temperature (47 ℃) and corn starch concentration (0.75% w/v) to obtain the glucose. The glucose concentration was measured by 3, 5-Dinitrosalicylic acid method. Resulted glucose was fermented (37 ℃) using Streptococcus thermophilus and the highest concentration of lactic acid was obtained after four days. The lactic acid yield was determined using UV visible spectrophotometer and calculated as 128.4 g/L. Lactic acid was purified by centrifugation followed by fractional distillation and characterized by Fourier Transform Infrared spectroscopy. Therefore, lactic acid could be successfully extracted from Sri Lankan corn starch using Streptococcus thermophilus.
Keywords: Corn starch; α-amylase; Streptococcus thermophilus; Lactic acid